AGE RELATED CHARACTERISTICS OF CHILDREN AND ADOLESCENT WITH HENOCH SCHÖNLEIN PURPURA AND SYSTEMS INVOLVEMENT: AN EXPERIENCE FROM TERTIARY CARE CENTER - Abdul Aziz, Danish; Siddiqui, Fatima; Tariq Siddiqui, Marium (Journal of Ayub Medical College Abbottabad, 2022)
Background: Henoch-Schönlein Purpura (HSP) is the most common vasculitis among children and adolescent characterized by skin, joints, renal and gastrointestinal involvement. There is different presenting feature of Henoch-Schönlein Purpura (HSP) and systemic involvement may vary at a certain age group. Methods: This was a ten-year retrospective cohort study done at a tertiary care hospital of Pakistan conducted from 2011-2020. Patients admitted with the diagnosis of Henoch-Schönlein Purpura (HSP) and in accordance with inclusion criteria were divided into groups based on their age, gastrointestinal symptoms and renal symptoms with the objective to compare the clinical features and investigations of Henoch-Schönlein Purpura (HSP) patients. Younger age group had patients age 7 years and less while the other group included patients who were older than 7 years. p-value <0.05 was considered as significant and SPSS 23 was used to analyzed the data. Result: Total 104 patients diagnosed with Henoch-Schönlein Purpura (HSP) were studied. Henoch-Schönlein Purpura (HSP) was more prevalent in males with an increased frequency during autumn and winter. Purpuric rash was present in more than 90% of the patients involved. Joint swelling was significantly (p=0.029) more common in the younger age group (73.3%) while renal involvement was seen more frequent in the older age group (57.1%) (p=0.002). Renal symptoms were less commonly seen in patients with GI involvement. There was no significant difference in platelet count, WBC count and ESR levels among any of the groups. Conclusion: Age related difference in presentation help us to anticipate more renal involvement in older children and adolescent likewise joint involvement is more commonly seen in younger children.